2017
DOI: 10.1103/physrevlett.119.204502
|View full text |Cite
|
Sign up to set email alerts
|

Revision of Bubble Bursting: Universal Scaling Laws of Top Jet Drop Size and Speed

Abstract: The collapse of a bubble of radius R_{o} at the surface of a liquid generating a liquid jet and a subsequent first drop of radius R is universally scaled using the Ohnesorge number Oh=μ/(ρσR_{o})^{1/2} and a critical value Oh^{*} below which no droplet is ejected; ρ, σ, and μ are the liquid density, surface tension, and viscosity, respectively. First, a flow field analysis at ejection yields the scaling of R with the jet velocity V as R/l_{μ}∼(V/V_{μ})^{-5/3}, where l_{μ}=μ^{2}/(ρσ) and V_{μ}=σ/μ. This resolve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

21
137
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(158 citation statements)
references
References 28 publications
21
137
0
Order By: Relevance
“…The physics involved has been discussed by several authors who have provided successive insightful approaches [8,[12][13][14][15][16]. A synthesis of the existing arguments was briefly discussed in [17]: those arguments pointed to the existence of an overall speed of the capillary wave front that should be of the order of . In other words, one should have t D > t o , which immediately implies that the Ohnesorge number Oh = µ (ρσRo) 1/2 should be below a critical one (here, Oh 1 ) to have a sufficiently energetic jetting for droplet ejection.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…The physics involved has been discussed by several authors who have provided successive insightful approaches [8,[12][13][14][15][16]. A synthesis of the existing arguments was briefly discussed in [17]: those arguments pointed to the existence of an overall speed of the capillary wave front that should be of the order of . In other words, one should have t D > t o , which immediately implies that the Ohnesorge number Oh = µ (ρσRo) 1/2 should be below a critical one (here, Oh 1 ) to have a sufficiently energetic jetting for droplet ejection.…”
mentioning
confidence: 99%
“…Among others, Krishnan et al [15] neatly described (see their figure 8) how the different wavelengths λ i of the wave packet produced by the breakup of the liquid film sequentially arrive at the axis segregated by their different wave speeds (σ/(ρλ i )) 1/2 . In [17], I observed that when the front of the main capillary wave producing ejection collapses at the axis, the curvature reversal of the surface involved in the onset of ejection imply that all terms of the momentum equation should be locally comparable. In brief, the collapse of a wave with speed V L and amplitude L leading to the ejection of a mass with characteristic radial size R and axial speed V should obey the dimensional balance:…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Close to the impact moment at t = 0, the schematic is shown in Fig.11(d), the capillary-driven surface deformation leads to the formation of two dimples. The dimple moves with v d velocity which can be defined as v d ∼ σ/ρR (capillary wave speed with the wave number of R −1 ) [18]. So, we can scale the shear stress as τ ∼ µv d /h.…”
Section: Iv4 Shear Force and Shear Ratementioning
confidence: 99%